Effect Modification of Sex and Age for the Hospital Volume‐Outcome Relationship in Abdominal Aortic Aneurysm Treatment: Secondary Data Analysis of the Nationwide German Diagnosis Related Groups Statistics From 2005 to 2014. Issue 6 (17th March 2020) - Trenner, Matthias; Salvermoser, Michael; Busch, Albert; Reutersberg, Benedikt; Eckstein, Hans‐Henning; Kuehnl, Andreas
Abstract : Background: Trials and registries associated female sex and high age with unfavorable outcomes in abdominal aortic aneurysm treatment. Many studies showed an inverse correlation between annual hospital volume and in‐hospital mortality. The volume‐outcome relationship has not been investigated separately for women and men or across the age range. The aim was to analyze whether sex and age are effect modifiers or confounders of the volume‐outcome association. Methods and Results: In a nationwide setting, all in‐hospital cases from 2005 to 2014 with a diagnosis of intact abdominal aortic aneurysm and procedure codes for endovascular or open aortic repair were included. Primary outcome was in‐hospital mortality. Using a multilevel multivariable regression model, hospital volume was modeled as a continuous variable. Separate analyses were performed for women and men and for predefined age groups. A total of 94 966 cases were included (12% women; median age, 72 years). Mortality was 4.9% in women and 3.0% in men (3.2% overall). Mortality increased with age. Although there was no significant volume‐outcome association in women ( P =0.57), there was in men ( P =0.02). The strongest volume‐outcome association was found in younger men. The younger female subpopulation was found to show a trend for an inverse volume‐outcome relationship, whereas an opposite association was found for the women aged >79 years. Conclusions: Women have a higher mortality risk after elective abdominal aortic aneurysm treatment. Sex and age are modifiers of the volume‐outcome relationship. Unlike in male patients, in women there is no consistent effect of hospital volume on outcome.